The evaluation of pendewasaan usia perkawinan (PUP) program in Jambi City - Choyrin Nizwa, Rizda; Noerjoedianto, Dwi; Wardiah, Rizalia; Ena Sari, Rumita; Siregar, Sri Astuti (Science Midwifery, 2023)
Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) stated that the ideal age for women to be married is 21 years old, while for men it is 25 years old. According to the report from Siga BKKBN, married woman in Jambi Province reached 598.395 people, there were 6.359 people who were married between the ages of 15 - 19 years and Jambi City was the region that had the highest number of married woman (more than 80.000 people) but had the lowest number of woman who getting married at the age of 15-19 years, that is only 0.2% of married woman. This is in line with the implementation of the Pendewasaan Usia Perkawinan (PUP) program organized by the BKKBN, the purpose of the program is to ensure that marriage takes place at the ideal age. The aim of this research is to evaluate the sustainability of the PUP program in Jambi City. The research was conducted using qualitative methods with a grounded theory research design. The results show that the input and process of the PUP program has gone well, however, in terms of cross-sector relations with government agencies that have a supporting role in the PUP program, it is known that there is still sectoral ego and policy overlap.